Covid-19 vaccine acceptance and hesitancy among medical students of Faisalabad - Din, Mohi Ud; Shahid, Umer; Qudoos, Abdul; Ahmed, Roman; Sohail, Muazzama; Javed, Saima (Journal of Rawalpindi Medical College, 2023)
Objectives: The study was conducted to determine the Covid-19 vaccine acceptance and hesitancy among the medical students who are more susceptible to be infected being the frontline workers. Methodology: This analytical cross sectional study was conducted in medical students of 1st to final year MBBS of various medical institutions of Faisalabad. Study duration was 3 months (August 2021 to October 2021). The sample size was 391 and divided in 2 age groups i.e. above and below 21 years and 245 (62.7%) comprised of females. The inclusion criteria were those students who gave consent and filled out the questionnaire and the exclusion criteria was who didn’t concede. The data was analysed on SPSS 25. Confidence interval was set to be 95% with 5% margin of error. Results: More than half of the participants i.e. 214 (54.7) have got Sinopharm vaccine. Vaccine hesitancy was found in 28 (7.2%) students and major reason was concern about vaccine safety. Significant relationship (p = < 0.05) was found in all factors related to ‘concerns regarding Covid-19 vaccines and trust of official information’; in all except one in factors related to ‘awareness and overall attitude regarding vaccine acceptance’ and in all except one in factors related to ‘perception of vulnerability to COVID-19 and attitude regarding usefulness of vaccine for community’. Conclusion: Covid-19 vaccine hesitancy was found in one out of every 14 medical students. They were concerned about the efficacy of Covid-19 vaccines. Most of the participants also showed concerns regarding severe adverse effects of these vaccine and on vaccine trials also before making it available for general public. At the same time, participants showed trust on information about Covid-19 vaccine from government and public health experts. Although vaccine hesitancy was present in only 7.2% of participants, health education programmes should be arranged to improve awareness and trust on Covid-19 vaccine. Concerns of medical students should be addressed on priority as future health care providers. Keywords: Covid-19, medical students, vaccine acceptance, hesitancy